Disputes and narratives on the distributed generation of electricity in Brazil: setbacks for the 2030 Agenda for sustainable development and the Paris Agreement - Soares, Alexsandra Maria de Almeida; Barreto, Cristiane Gomes (Sustainability in Debate, 2022)
Centralization and low diversification of the Brazilian electricity matrix have increased the feeling of energy insecurity. This is a problem that is gaining greater proportions in face of climate change. This research analyzed the political arena around the regulation of distributed electricity generation. We analyzed documents, speeches, interviews, presentations, audiovisual material and press publications on distributed generation and solar power. Results indicated that, despite the great development potential of the source in the country, and the international commitments signed, the identified coalitions dispute narratives that result in setbacks for the climate and sustainable development agendas.